2021
DOI: 10.1088/1757-899x/1075/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Design Mixture of RAP-HMA Pavements: A Review

Abstract: Roads are the national assets of a country. Once they are non-functional, they can be recycled to serve the next design life. Flexible pavements are the predominant type of pavement all over the world. The distressed flexible pavement material can be termed as Reclaimed Asphalt Pavement (RAP) material. The most common percent of RAP in the recycling process is 20% only. For higher incorporation of RAP material, there is uncertainty in the performance of RAP-HMA mixture. Design Mixture of RAP incorporated HMA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Further they investigated that higher percentages of RAP causes uncertainty in the mix. The uncertainty depends upon type and dosage of rejuvenating agent, method of intrusion of RAP material in plant production units and viscosity of aged binder [17]. Tao et al and Mogawer et al studied the combined effect of high RAP contents and different types of WMA additives on the workability of asphalt mix and concluded that WMA technologies lower the mixing and compaction temperature and improve workability of mix containing RAP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Further they investigated that higher percentages of RAP causes uncertainty in the mix. The uncertainty depends upon type and dosage of rejuvenating agent, method of intrusion of RAP material in plant production units and viscosity of aged binder [17]. Tao et al and Mogawer et al studied the combined effect of high RAP contents and different types of WMA additives on the workability of asphalt mix and concluded that WMA technologies lower the mixing and compaction temperature and improve workability of mix containing RAP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of higher percentages of RAP would lead to greater environmental and economic benefits, this may negatively affect the performance of the pavement if not properly designed ( 1 ). The fragility and high stiffness of the RAP binder, owing to the weather and traffic action during the pavement service life, may promote damage in the new pavement, mainly in the form of fatigue and thermal cracking ( 2 ). For this reason, higher amounts of RAP in recycled mixtures are a cause for concern for pavement contractors: currently, the percentage of RAP in a mix specified in the standards of several countries ranges between 15% and 30% in top lifts ( 25 ).…”
mentioning
confidence: 99%